Biochemical parameters of blood serum of young cattle with trichurosis invasion - Шевченко, Т. С. (Scientific Progress & Innovations, 2016)
The paper presents data of biochemical parameters of blood serum of cattle 6-12 months of age with tryhurosis invasion. We established that the parasites pathogens leads to changes in the biochemical parameters in animals, including: in patients of young cattle with tryhurosis, compared with clinically healthy animals, in serum of blood significantly reduced amount of albumin (32,7 %, P<0,01), urea nitrogen (23,8 %, P<0,05), creatinine (44,1 %, P<0,05), calcium (28,6 %, P<0,001) and carotene (32,4 %, P<0,05). At the same time we established a significant increase of AST (in 2,7 times, P<0,001) and index de Ritis (in 2,4 times, P<0,001).